ANALISIS PERENCANAAN REKRUTMEN APARATUR SIPIL NEGARA KABUPATEN MAMUJU UTARA (Studi pada Badan Kepegawaian Dan Diklat Daerah Kabupaten Mamuju Utara) - Nahidah, Nahidah (Katalogis, 2016)
This study aimed to describe, analyze and interpret the State Civil Administrative Recruitment Planning in the Government of North Mamuju regency in 2014. The method used in this study is a qualitative research method with descriptive approach. Qualitative research method is used because researchers would like to obtain an in-depth overview of the planning in the process of recruitment of civil servants in the Civil Service Agency and the Regional Training North Mamuju regency. Resource persons were selected in this study a number of informants selected 6 people considered to know and understand the issues regarding the research focus and the informant believed to provide the required data. Based on the analysis and discussion of the planning of recruitment ASN in North Mamuju regency, the authors conclude that the recruitment planning analysis ASN in North Mamuju regency implemented by BKDD has not been done well under the three stages recommended by Simamora. Document Anjab / crew that has been done by Section Ortala have drawbacks such as a mismatch between existing titles in the document Anjab/crew to that used in the application of E-Formation owned by Kemenpan RB. As a result of these weaknesses, the BKDD can not compose projected needs of civil servants using the results Anjab/the crew. BKDD must make improvements prior to the document Anjab/crew are to be adjusted with the E-Formation. In the data collection occurred availability of human resources data discrepancies between data held by BKDD with the real situation on the ground. This difference is caused by mutations in the transfer of personnel who are not procedural, supposed to be with a decree by BKDD however that the displacement of the educators / teachers among school and health personnel among UPTD health or Pukesmas (Pustu) only with the Memorandum of the Office of the Head Office without No notification to BKDD.